PENGARUH PEMBERIAN MADU TERHADAP PENURUNAN TEKANAN DARAH PADA BU HAMIL HIPERTENSI DI WILAYAH KERJA PUSKESMAS BAJOE KABUPATEN BONE - Fitrah, Fitrah Ramadani; Andi Haryati Hasrib; Megawati, Megawati; Dewi Mulfiyanti (Nusantara Hasana Journal, 2025)
Hypertension in pregnancy is common and is included in the causes of maternal death during childbirth, and has other serious effects. The proportion of hypertension in pregnancy in Indonesia is increasing, almost 30% of maternal deaths in Indonesia are caused by hypertension, Based on data from the Bone Regency Health Office in 2023, there were 11,992 pregnant women and 112 pregnant women with hypertension and Based on data from the Bajoe Health Center UPT, Bone Regency in 2022, there were 665 pregnant women and 15 pregnant women with hypertension and in 2023 the number of hypertension was 9 people. The purpose of this study was to determine the effect of honey administration on reducing blood pressure in hypertensive pregnant women. The research method is a quasi-experimental study using a one group pre and post test design, with a sample of 10 samples that were given honey, before the administration, blood pressure was measured first. Research Results after giving honey for 5 consecutive days with 2 tablespoons in the morning and 2 tablespoons in the afternoon there was a decrease in blood pressure with a p_Value of 0.002, which means (p <0.005). So consuming honey twice a day for 5 consecutive days can lower blood pressure in pregnant women with hypertension.